Development of the banana plants 'Prata Anã' and 'FHIA-01' under the effect of paclobutrazol applied on the soil - Maia, Emanuel; Siqueira, Dalmo L.; Salomão, Luiz C.C.; Peternelli, Luiz A.; Ventrella, Marília C.; Cavatte, Rithiely P.Q. (Anais da Academia Brasileira de Ciências, 2008)
Under some cultivation conditions, excessive growth of the pseudostem of banana plants can be considered a limiting factor, and thus, the use of growth regulators can constitute a valid alternative. This work aimed to evaluate the action of paclobutrazol on the growth of the pseudostem of banana plants and other characteristics of their development. An experiment was installed with five paclobutrazol doses (0; 0.5; 1.0; 1.5; and 2.0 g of a.i. plant-1) combined with two banana plant cultivars ('Prata Anã' and 'FHIA-01'). Paclobutrazol did not affect the number of days from planting to flowering, total leaf area and leaf emission rate. However, it increased leaf permanence on the plants and sucker number, reduced the foliar area of the leaves emitted after its application and provided an average reduction in pseudostem height of 26%.

Em algumas condições de cultivo o crescimento excessivo do pseudocaule de bananeiras pode ser considerado um fator limitante, assim a utilização de reguladores de crescimento pode constituir uma alternativa. O presente trabalho teve por objetivo avaliar a ação do paclobutrazol sobre o crescimento do pseudocaule de bananeiras e outras características do seu desenvolvimento. Para isso foi instalado um experimento com cinco doses do paclobutrazol (0; 0,5; 1,0; 1,5; e 2,0 g de i.a.planta-1) combinadas com dois cultivares de bananeira ('Prata Anã' e 'FHIA-01'). O paclobutrazol não afetou o número dedias do plantio ao florescimento, a área foliar total e a taxade emissão de folhas. Contudo, aumentou a permanência das folhas nas plantas e o número de perfilhos, reduziu a área foliar das folhas emitidas após a sua aplicação e proporcionou uma redução média de 26% na altura do pseudocaule.
Keywords: Foliar area; Growth analysis; Growth regulator; Musa spp.; Suckers